Beta-Lactamases: Determination of Their Isoelectric Points - Barthelemy, Michel (1978)
Important discrepancies in isoelectric points (pI) of β-lactamases were observed depending on the experimental procedure used for their determination: isoelectric focusing (IEF) in sucrose density gradients or analytical IEF in thin-layer polyacrylamide gels (PA). The variations, negligable in the case of TEM-like β-lactamases, appeared to be important in the case of cephalosporinases and are related to an artifact which appears in PA-IEF. This has been clearly shown with β-lactamase preparations from the following bacterial strains: Pseudomonas aeruginosa NCTC 8203 (pI = 8.7), P. aeruginosa NCTC 10701 (pI = 9.4), and Proteus morganii NCTC 235 (pI = 8.3). The data previously obtained by PA-IEF were much lower.